BIOCHEMISTRY OF HEPATIC DETOXIFICATION: BIOTRANSFORMATION (PHASE I–II) ENZYME SYSTEMS, OXIDATIVE STRESS, AND ITS ASSOCIATION WITH HYPERBILIRUBINEMIA (International journal of artificial intelligence, 2026)
The liver is the main organ that detoxifies foreign chemicals and endogenous metabolites through biotransformation. This process includes Phase One functionalization reactions and Phase Two conjugation reactions, followed by transporter mediated excretion into bile or blood. Phase One reactions, driven largely by the cytochrome P450 monooxygenase system, introduce or expose polar groups through oxidation, reduction, or hydrolysis. However, cytochrome P450 activity can generate reactive intermediates and reactive oxygen species when electron transfer is inefficient, promoting oxidative stress and cellular damage. Phase Two reactions generally reduce toxicity by conjugating metabolites with highly polar groups via enzyme families such as uridine diphosphate glucuronosyltransferases, sulfotransferases, glutathione transferases, N acetyltransferases, and methyltransferases, thereby increasing water solubility and facilitating elimination. Hyperbilirubinemia is closely linked to detoxification because bilirubin requires hepatic uptake, glucuronidation by uridine diphosphate glucuronosyltransferase family one member A one, and biliary secretion. Oxidative stress can impair detoxification enzymes and transporters and modify gene expression through redox sensitive signaling pathways, including nuclear factor erythroid two related factor two, which alters antioxidant and detoxification capacity. Together, Phase One and Phase Two metabolism, antioxidant defenses, and bilirubin handling form an integrated biochemical network that explains many clinical manifestations of liver dysfunction, particularly oxidative injury and hyperbilirubinemia.